Outcomes of first versus third kidney transplantations: propensity score matching and paired subgroup analysis—a single-centre experience - Telkes, Gábor (Langenbecks Arch Surg, 2021)
BACKGROUND: In the Eurotransplant, 12.6% of kidney transplantations are a repeat procedure. Third transplants are significantly more complex than first and second ones. We compared the results of first (PRT) versus third (TRT) transplantations. METHODS: Between 2011 and 2016, we performed 779 deceased donor adult kidney transplantations, 14.2% out of them were second, 2.6% (20) third, and 0.3% fourth. We compared the pre-, intra-, and postoperative data, kidney function, and survival rate. RESULTS: Recipients of TRT were younger (53.4 vs. 47.3 p = 0.02). HCV infection rate (20%, p = 0.00) is ten times higher. The operation time is longer (132 vs. 152 min, p = 0.02), and delayed graft function is much more frequent (22.4% vs. 60%, p = 0.00). Induction therapy was given to every TRT (7.9% vs.100%), but as a result, the rejection rate was the same (~ 15%). Hospital stay is a week longer. Patient’s survival at 1, 3, and 5 years for PRT is 96.4%, 93.9%, and 91.2% and for TRT is 90%, 85%, and 78.4%, respectively (p = 0.023). TRT’s odds ratio of fatal outcome is 4.35 (1.5–12.5). Graft survival at 1, 3, and 5 years for PRT is 93.1%, 91.4%, and 90.3% and for TRT is 75%, 75%, and 75%, respectively (p = 0.020). TRT’s odds ratio of graft loss is 3.14 (1.1–8.9). Of PRT 85.76%, out of PRT 85.76%, while out of TRT 60% live with a functioning graft, p=0.00149. CONCLUSION: In a third transplant, both graft and patient survival are significantly inferior to primer ones. Careful selection is required to minimize the patient risk and graft loss.